The near-isotropic elastic properties of interpenetrating composites reinforced by regular fibre-networks. (September 2022) - Zhang, Zhengyang; Zhu, Hanxing; Yuan, Ru; Wang, Sanmin; Fan, Tongxiang; Rezgui, Yacine; Zhang, Di
Graphical abstract: Highlights: All IPCs can have an almost isotropic Young's modulus larger than the Voigt limit. The range and largest values of the normalised Young's moduli of the IPCs are identified. Structural hierarchy of the IPCs can enhance their stiffness. Abstract: It is highly demanding and challenging to maximise the stiffness of the interpenetrating phase composites (IPCs) while still keeping their isotropy. In this paper, the elastic properties of IPCs reinforced by three different types of regular lattice fibre networks are investigated by computer simulation and analytical methods. The numerical results indicate that the larger the difference between the Poisson's ratios and the smaller the difference between the Young's moduli of the constituent materials, the larger the Young's moduli of these IPCs are. It is also found that structural hierarchy can enhance the stiffness of these IPCs by 30%. In addition, the three types of IPCs have Zener anisotropy factors in the range of 1.0 ± 0.04 in most cases, could have an almost isotropic Young's modulus two times larger than the Voigt limit, and a Poisson's ratio with a positive or negative or zero value. Moreover, they are easy to manufacture, their Young's moduli are in general 1.0–3.0 times those of the conventional particle or short fibre reinforced composites and other types of IPCs including those reinforced by the triply periodic minimal surface (TPMS) shells, and the type of IPCs with the largest Young's modulus has been identified.